Melatonin administration reduces inflammatory pain in rats - Laste G; de Macedo IC; Ripoll Rozisky J; Ribeiro da Silva F; Caumo W; Torres IL (Journal of Pain Research, 2012)
Gabriela Laste,1–3 Isabel Cristina de Macedo,1,3 Joanna Ripoll Rozisky,1–3 Fernanda Ribeiro da Silva,1,3 Wolnei Caumo,1,2 Iraci LS Torres1–31Laboratório de Farmacologia da Dor, Departamento de Farmacologia, Instituto de Ciências Básicas da Saúde, 2Programa de Pós-Graduação em Medicina, Ciências Médicas, Universidade Federal do Rio Grande do Sul, Porto Alegre, Brazil; 3Unidade de Experimentação Animal e Grupo de Pesquisa e Pós-Graduação, Hospital de Clínicas de Porto Alegre, Porto Alegre, BrazilAbstract: In view of the broad range of effects attributed to melatonin, this study evaluated its analgesic effect on inflammatory pain induced by complete Freund's adjuvant (CFA) in Wistar rats. Inflammation was induced by intradermal CFA injection in the hind paw of all animals, which were then divided into two groups that received either 60 mg/kg of melatonin or vehicle (1% alcohol in saline), intraperitoneally, for three days. The analgesic effect of melatonin was assessed by the hot-plate test, immediately and thereafter at 30, 60, 90, and 120 minutes after the first administration and 24 hours after once-daily administration for 2 more days. After CFA injection, melatonin administration increased withdrawal latency at 60 minutes after the first dose. After the end of treatment, melatonin showed a significant analgesic effect on inflammatory pain. This study paves the way for exploration of how brief courses of treatment could improve this analgesic effect in the late phases of inflammatory pain.Keywords: analgesic response, complete Freund's adjuvant, hot-plate test, inflammation, melatonin, nociception